NKG2D knockdown improves hypoxic-ischemic brain damage by inhibiting neuroinflammation in neonatal mice - Lin Liu; Yuxin Yang; Ting Wu; Junrong Du; Fangyi Long (Scientific Reports, 2024)
Abstract Hypoxic-ischemic brain damage (HIBD) is a leading cause of neonatal death and neurological dysfunction. Neuroinflammation is identified as one of the crucial pathological mechanisms after HIBD, and natural killer group 2 member D (NKG2D) is reported to be implicated in the pathogenesis of immunoinflammatory diseases. However, the role of NKG2D in neonatal HIBD is seldomly investigated. In this study, a neonatal mice model of HIBD was induced, and the role of the NKG2D in neuroinflammation and brain injury was explored by intracerebroventricular injection of lentivirus to knockdown NKG2D in neonatal mice with HIBD. The results showed that a significant increase in NKG2D protein level in the brain of neonatal mice with HIBD. The NKG2D knockdown in the brain significantly alleviated cerebral infarction, neurobehavioral deficits, and neuronal loss in neuronal HIBD. Moreover, the neuroprotective effect of NKG2D knockdown was associated with inhibition of the activation of microglia and astrocytes, expression of NKG2D ligands (NKG2DLs) and DAP10, and the nuclear translocation of NF-κB p65. Our findings reveal NKG2D knockdown may exert anti-inflammatory and neuroprotective effects in the neonatal mice with HIBD through downregulation of NKG2D/NKG2DLs/DAP10/NF-κB pathway. These results suggest that NKG2D may be a potential target for the treatment of neonatal HIBD.